APAKAH MODEL DELONE DAN MCLEAN MAMPU MENJELASKAN KEBERHASILAN SISTEM INFORMASI JKN MOBILE ? - Desiana E. Sugesti; Ulfah Hidayati; Sugiarti Sugiarti (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2020)
We investigate the Delone & Mclean success system model on JKN-Mobile in the Indonesian Social Security Provider for Health - BPJS. The research was conducted through a direct survey of users of the JKN mobile system to the Health Social Security Administrators at the Semarang City Office. The data is processed using Structural Equation Modeling, namely the SmartPLS application. The results showed that the quality of JKN Mobile services affected the system to use. User satisfaction is determined by the quality of information, system quality, and service quality of the JKN Mobile system, which affects the benefits of the JKN Mobile system. This study has contributed to the success of the system at the success model JKN mobile applications used extensively and intensively.